Cross-linguistic Metaphorical Representation of the #MeToo Movement: Communicating Attitudes - Cibulskienė, Jurga (Respectus Philologicus, 2020)
The article focuses on the metaphorical conceptualisation of the #MeToo movement, which has spread virally as a hashtag used on social media in an attempt to demonstrate the widespread prevalence of sexual assault and harassment. The #MeToo movement as a social issue is looked at from the perspective of Critical Metaphor Analysis (CMA) (Charteris-Black 2005/2011, 2014, Musolff 2004, 2016, Koller 2014, De Landtsheer 2009, Hart 2010). CMA is a blend of Cognitive Metaphor Theory and Critical Discourse Analysis that aims at identifying how metaphors are used to describe socially contested issues and how they reveal speakers’ hidden intentions and attitudes (Charteris-Black, 2014, p. 174). CMA is also concerned with the different functions metaphors may perform. A predicative function, being one of many, is most likely to explain how socially sensitive issues are communicated (Charteris-Black, 2014, pp. 204-207; Musolff, 2016, p. 4). In other words, it implies positive or negative attitudes expressed towards certain issues. Thus, the paper aims to study how the predicative function of metaphor manifests in the discourse of contemporary social concerns cross-linguistically and cross-culturally. In other words, the paper looks into how different attitudes towards the #MeToo movement are communicated via metaphors in Lithuanian and English media and how they shape prevailing public attitudes.